Managing Acute Intermediate Risk Pulmonary Thromboembolism in a Patient Who Developed Heparin-Induced Thrombocytopenia: Review of Current Guidelines and Literature - Blerina Asllanaj MD; Elizabeth Benge MD; Sapna Bhatia MD; Yi McWhorter DO (SAGE Publishing, 2023)
Intermediate-risk pulmonary embolism describes hemodynamically stable patients with evidence of right ventricular strain, whereas high-risk pulmonary embolism comprises hemodynamic decompensation resulting in cardiogenic shock. The clinical manifestations of the two aforementioned conditions are challenging to treat in the setting of heparin-induced thrombocytopenia (HIT). Without immediate therapeutic anticoagulation, patients can subsequently deteriorate and require additional advanced therapies, with the end-goal of restoring pulmonary artery perfusion. We present the case of a male with bilateral intermediate-risk pulmonary emboli who developed type 2 HIT prompting different selection of appropriate management strategies.